Tuberculous Meningitis in Children: A Forgotten Public Health Emergency - du Preez, Karen; Jenkins, Helen E.; Donald, Peter R.; Solomons, Regan S.; Graham, Stephen M.; Schaaf, H. Simon; Starke, Jeffrey R.; Hesseling, Anneke C.; Seddon, James A. (Frontiers in Neurology, 2022)
Tuberculous meningitis (TBM) remains a major cause of morbidity and mortality in children with tuberculosis (TB), yet there are currently no estimates of the global burden of paediatric TBM. Due to frequent non-specific clinical presentation and limited and inadequate diagnostic tests, children with TBM are often diagnosed late or die undiagnosed. Even when diagnosed and treated, 20% of children with TBM die. Of survivors, the majority have substantial neurological disability with significant negative impact on children and their families. Surveillance data on this devastating form of TB can help to quantify the contribution of TBM to the overall burden, morbidity and mortality of TB in children and the epidemiology of TB more broadly. Paediatric TBM usually occurs shortly after primary infection with Mycobacterium tuberculosis and reflects ongoing TB transmission to children. In this article we explain the public health importance of paediatric TBM, discuss the epidemiology within the context of overall TB control and health system functioning and the limitations of current surveillance strategies. We provide a clear rationale for the benefit of improved surveillance of paediatric TBM using a TB care cascade framework to support monitoring and evaluation of paediatric TB, and TB control more broadly. Considering the public health implications of a diagnosis of TBM in children, we provide recommendations to strengthen paediatric TBM surveillance and outline how improved surveillance can help us identify opportunities for prevention, earlier diagnosis and improved care to minimize the impact of TBM on children globally.